Determination of Anthropometric Measurements and Nutritional Status of Wheelchair Basketball Players - İSLAMOĞLU, AYŞE HÜMEYRA (My University, 2023)
The aim of this study was to determine the anthropometric measurements, nutritional habits, and nutritional knowledge levels of wheelchair basketball players. Anthropometric measurements and 24-hour food consumption records were taken from 29 wheelchair basketball players and a structured questionnaire about nutritional habits and knowledge levels was applied to 40 wheelchair basketball players by face-to-face interview. The median values of the anthropometric measurements of basketball players were within the reference range (21.6 kg/m2 for female players, 22.7 kg/m2 for male players). Fifty-two percent of basketball players find their nutritional knowledge level sufficient, 47.5% use media for the source of nutritional information, 45% skip lunch, and 12.5% drink water >2 L/day. The health complaints of basketball players were mostly frequent cramps (17.5%) and cold (17.5%). Nutrients that the majority of basketball players consumed below the estimated average requirements were found to be carbohydrate, fiber, thiamine, calcium, vitamin C, and vitamin D. It is concluded that not all basketball players have sufficient nutritional knowledge, and those who do, cannot reflect this knowledge very accurately on their nutritional habits. It will be better for wheelchair basketball players to receive nutritional education. More research is needed to make more accurate evaluations of the nutritional status of athletes with disabilities.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Demografi; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Social Sciences and Humanities; Sociology; Demography; Health Sciences; Klinik Tıp (MED); Sosyal Bilimler (SOC); Klinik Tıp; Sosyal Bilimler Genel; REHABİLİTASYON; ORTOPEDİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; DEMOGRAFİ; Clinical Medicine (MED); Social Sciences (SOC); CLINICAL MEDICINE; SOCIAL SCIENCES, GENERAL; REHABILITATION; ORTHOPEDICS; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; DEMOGRAPHY; Sağlık (sosyal bilimler); Sosyal Bilimler ve Beşeri Bilimler; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Ortopedi ve Spor Hekimliği; Yaşam Boyu ve Yaşam Boyu Çalışmaları; Health (social science); Social Sciences & Humanities; Physical Therapy, Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine; Life-span and Life-course Studies; Anthropometry; Basketball; Nutrition; Wheelchairs